2002
DOI: 10.2134/jeq2002.1610
|View full text |Cite
|
Sign up to set email alerts
|

Relating Net Nitrogen Input in the Mississippi River Basin to Nitrate Flux in the Lower Mississippi River

Abstract: A quantitative understanding of the relationship between terrestrial N inputs and riverine N flux can help guide conservation, policy, and adaptive management efforts aimed at preserving or restoring water quality. The objective of this study was to compare recently published approaches for relating terrestrial N inputs to the Mississippi River basin (MRB) with measured nitrate flux in the lower Mississippi River. Nitrogen inputs to and outputs from the MRB (1951 to 1996) were estimated from state-level annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 37 publications
6
91
0
Order By: Relevance
“…Pasture/ rangelands include nutrients from nonrecoverable animal manure-i.e., manure from unconfined animals and manure lost during the collection, storage, and treatment of wastes from confined animals, including concentrated animal feeding operations (22). The model assumes that nutrient immobilization and mineralization rates in soils of the MARB are approximately in equilibrium as in prior MARB models (18,23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasture/ rangelands include nutrients from nonrecoverable animal manure-i.e., manure from unconfined animals and manure lost during the collection, storage, and treatment of wastes from confined animals, including concentrated animal feeding operations (22). The model assumes that nutrient immobilization and mineralization rates in soils of the MARB are approximately in equilibrium as in prior MARB models (18,23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Total ammonium deposition in the MARB represents less than 10% of the nitrogen inputs to cropland from commercial and manure fertilizers and biologically fixed N2. Much of the deposition originates from livestock ammonia emissions, which are more than double those from fertilizer (37), with about half of the deposition occurring within 50 km of the emission source (23). Ammonium deposition was not explicitly included in the model inputs to cropland because of uncertainties in agricultural sources and transport distances (i.e., long-range vs local deposition).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with process-based models, statistical models are predominant for addressing watershed legacy nutrient dynamics. Based on long-term (>30 years) observations, statistical models between annual riverine nitrate flux and previous several years' average net anthropogenic nitrogen inputs (NANI) were developed to address N leaching lag effect in the Mississippi River watershed (previous 2-5 and 6-9 years' average NANI) in 1960-1998(McIsaac et al, 2001) and the Yongan watershed (previous 0-6 years' average NANI) in eastern China in 1980(Chen et al, 2014b. Other several statistical models were directly established between annual riverine nutrient flux and current year's NANI or NAPI, hydroclimatic, and land-use variables in the Yongan watershed and Yangtze watershed in China (Chen et al, 2015b(Chen et al, , 2016c.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…Considering the difference of accumulated legacy nutrient pools across landscapes, Chen et al (2016a,b) further developed statistical models for linking net anthropogenic N or P inputs to agricultural/forest and residential systems with riverine TN or TP flux and then identified contributions of agricultural and residential legacy nutrient sources in Yongan watershed in eastern China in 1980-2010. In these statistical models, relationships between riverine nutrient flux and anthropogenic nutrient inputs were usually expressed as an exponential function, which may be a consequence of anthropogenic nutrient inputs exceeding the capacity of terrestrial and/or aquatic systems to assimilate or retain excessive nutrient (Chen et al, 2015b;McIsaac et al, 2001;Sharpley et al, 2013). ), NANI 0-6 is the average annual NANI during the previous 0-6 years (kg N ha À1 year À1 ), T 0-4 is the average air temperature during the previous 0-4 years (°C), and D % is the drained agricultural area percentage during the previous 0-3 years ), and NANI is the net anthropogenic nitrogen input (kg N km À2 year À1 ) …”
Section: Statistical Modelsmentioning
confidence: 99%
“…Also, due to the long mean residence time of fertilizer N in soils the effects of changes in soil management practices on nitrate loading of the hydrosphere may be considerably delayed. For instance, studies of the Mississippi River Basin have revealed a decrease in anthropogenic N inputs without any concurrent reductions in riverine nitrate loading (41)(42)(43).…”
mentioning
confidence: 99%